Pharmacy Faculty Burnout: Cause for Concern that Requires Our Support and Use of Best Evidence - Shane P. Desselle; Patricia L. Darbishire; Brooke H. Clubbs (University of Minnesota Libraries Publishing, 2020)
Recent attention has been afforded to the concept of burnout and other quality of worklife issues among pharmacy faculty, underscoring the importance of organizational culture, citizenship, collegiality, and support. Support comes from the larger academic institution, the college/school, and individual colleagues. Evidence points to reassurance of worth, guidance, and positive affirmation as being among the most salient factors in mitigating burnout of faculty, who are caught in the midst of increasing demands and higher administrative burdens. A supportive culture that reassures worth of individual faculty is not a unidimensional typology, but rather, is one that permeates through all components of a multifaceted and strong culture that encourages citizenship. There is a growing body of research and evidence on faculty burnout and related factors. This commentary calls for the use of such evidence in guiding policies, creating mentoring programs, and carrying out daily activities in much the same manner that scholars use the best available evidence in their own specific lines of inquiry in teaching and research.   Article Type: Commentary